2008
DOI: 10.1136/bjo.2007.125187
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of the effects of brinzolamide and dorzolamide on retinal oxygen saturation and ocular microcirculation in patients with primary open-angle glaucoma

Abstract: This pilot study suggests that brinzolamide and dorzolamide may increase retinal oxygen saturation in patients with OAG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
52
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(59 citation statements)
references
References 47 publications
4
52
0
3
Order By: Relevance
“…Brinzolamide as well as dorzolamide have also been found to increase ONH, choroidal and retinal blood flow in patients with glaucoma and experimental animals in several studies. [63][64][65][66][67] One study indicated that treatment with dorzolamide normalizes retinal blood flow regulation in patients with glaucoma. 68 This is in agreement with data showing that a 6-month treatment with dorzolamide normalizes the ocular pressure/flow relationship.…”
Section: Topical Therapiesmentioning
confidence: 99%
“…Brinzolamide as well as dorzolamide have also been found to increase ONH, choroidal and retinal blood flow in patients with glaucoma and experimental animals in several studies. [63][64][65][66][67] One study indicated that treatment with dorzolamide normalizes retinal blood flow regulation in patients with glaucoma. 68 This is in agreement with data showing that a 6-month treatment with dorzolamide normalizes the ocular pressure/flow relationship.…”
Section: Topical Therapiesmentioning
confidence: 99%
“…Brinzolamide (Brz), one of the carbonic anhydrase inhibitors, is effective in reducing IOP for glaucoma therapy mainly through decreasing the production of the aqueous humor (4). Its aqueous solubility is very low at pH 7.4 (25°C) probably due to its high lipophilicity.…”
Section: Introductionmentioning
confidence: 99%
“…Studies using various retinal oximetry devices to measure the oxygen saturation of the retinal vasculature in glaucoma have been reported. [12][13][14][15][16][17][18][19][20] Hyperspectral imaging combines spectroscopy with digital imaging whereby spectral data (using numerous contiguous wavelengths of light) are obtained in every pixel of an image plane. An oximetry study of the retinal vascular network using a hyperspectral imaging system (images acquired using more than three contiguous wavelengths) in glaucoma has not yet been reported.…”
Section: Introductionmentioning
confidence: 99%